Knowledge about sudden infant death syndrome prevention among postpartum women in Southern Brazil, 2019: a cross-sectional survey - Anelise Medeiros Souto; Luana Patrícia Marmitt; Christian Loret de Mola; Juraci Almeida Cesar (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To assess knowledge on sudden infant death syndrome (SIDS) prevention among postpartum women who received prenatal care in public and private services in Rio Grande, Rio Grande do Sul, Brazil, in 2019. Methods A cross-sectional study was conducted with postpartum women who gave birth in that municipality in 2019; the outcome was the indication of incorrect sleeping position (side/supine position) to prevent SIDS; the chi-square test was used to compare proportions between those who underwent prenatal care in public and private services. Results Among all 2,195 postpartum women, 67.7% (95%CI 65.7;69.6) were unaware of the position that prevents SIDS, 71.6% were public care service users; 77.8% of them feared choking/suffocation; 1.9% were informed about SIDS during prenatal care; doctors/nurses (70.5%) and grandmothers (65.1%) were influential regarding the baby's sleeping position. Conclusion Most postpartum women were unaware of the sleeping position that prevents SIDS, especially those receiving care in the public sector; in general, this subject is not discussed in prenatal care.